Passion and Persistence: Investigating the Relationship Between Adverse Childhood Experiences and Grit in College Students in China - Cheung, Shannon; Huang, Chien-Chung; Zhang, Congcong (Frontiers in Psychology, 2021)
Adverse childhood experiences (ACEs) are known to have deleterious effects on individuals across the life span, but less is known about how they affect grit, a strong predictor of achievements and well-being. This study seeks to investigate the effect of ACEs on grit in a sample of Chinese college students during the COVID-19 pandemic. Data were collected from 1,871 students across 12 universities in China. Findings indicated a significant effect of ACEs on grit, particularly abuse and neglect dimensions of ACE. Since grit is particularly important for professional success, those who have experienced abuse and neglect victimization may struggle throughout their education, and subsequently, in their careers. This calls for interventions to buffer the effects of ACEs on grit.